Pesca ilegal y activismo ciudadano ¿es posible conciliar nuevos acuerdos? - Maldonado Gordon, Alejandra Nicolle (2024)
The present work intends to analyze the influence of social actors in the process of public policies regarding illegal fishing. The creation of the Brotherhood Marine Reserve responds to the achievement of a minority coalition, which generated a change 6 years after its first mobilization against this activity. Faced with this, by qualitative research, the members of the Insular Front collective were taken as a case of study, in order to understand their activities to make this objective tangible. Through the Advocacy Coalition Framework approach, it was possible to analyze the public policy process as a whole, highlighting the participation of collective action within the system. In this way, by interviews, the study offers findings that enrich the academic discussion, since it allowed to understand that the composition of civil society and the government, in practice, manages to build real alternatives to this problem.